Activity against Mycobacterium tuberculosis with concomitant induction of cellular immune responses by a tetraaza-macrocycle with acetate pendant arms - David, S (2015)
The novel tetraaza-macrocyclic compound 3,7,11-tris(carboxymethyl)-3,7,11,17-tetraaza-bicyclo[11.3.1]heptadeca- 1(17),13,15-triene, abbreviated as ac(3)py14, was investigated for its activity against Mycobacterium tuberculosis and for induction of protective cellular immune responses. Perspective results show that ac(3)py14 and its Fe3+ 1:1 complex, [Fe(ac(3)py14)], inhibited radiometric growth of several strains of M. tuberculosis. Inhibition with 25 mug/mL varied from 99% for H37Rv to 80% and above for multiple drug-resistant clinical isolates. The capacity of ac(3)py14 to elicit a beneficial immune response without cellular apoptosis was assessed and compared to the effects of virulent M. tuberculosis. The present study produces evidence that after stimulation with ac(3)py 14 there was significant production of interferon gamma (IFN-gamma), whereas the production of interleukin-5 (IL-5) remained low, and there was development of a memory population (CD45RO). The level of binding of Annexin V, a marker of apoptosis, was not sufficient to result in toxic effects toward alpha beta and gamma delta T cells and CD14(+) macrophages. This preliminary study is the first report of a compound that simultaneously exerts an inhibitory effect against M. tuberculosis and induces factors associated with protective immune responses. (C) 2001 Editions scientifiques et medicales Elsevier SAS.